A legal and economic analysis of non-fungible tokens on the art market - Chembezi, Titose (School of Economics, 2025)
This thesis conducts a legal and economic analysis of Non-Fungible Tokens (NFTs) in the art market, exploring the integration of intellectual property rights and the financial implications of these digital assets. It examines the challenges of applying existing copyright laws, such as the right of first sale and fair use doctrines, to the novel context of NFTs, highlighting the need for enhanced regulatory practices within NFT marketplaces. Proposals include the development of reverse image search technologies to mitigate copyright infringement and foster a more robust legal environment. Economically, the thesis compares the valuation of NFTs to traditional art portfolios, acknowledging the difficulty in assessing their intrinsic value due to subjective perceptions and speculative influences. To counteract speculative volatility and establish more grounded valuations, it suggests the adoption of a hybrid approach that combines the expertise of curators with machine learning models and standardized valuation frameworks. The analysis concludes that while NFTs provide significant opportunities for artists by increasing market access and liquidity, the current environment is fraught with legal uncertainties and economic instability. The thesis advocates for the ongoing evolution of economic and legal frameworks to fully leverage the benefits of NFTs in the art market, ensuring they contribute positively to the sustainability and growth of artists' careers and stakeholders.